Interbank tiering and money center banks - Ben R. Craig; Goetz von Peter (Deutsche Bundesbank, 2010)
This paper provides evidence that interbank markets are tiered rather than flat, in the sense that most banks do not lend to each other directly but through money center banks acting as intermediaries. We capture the concept of tiering by developing a core-periphery model, and devise a procedure for fitting the model to real-world networks. Using Bundesbank data on bilateral interbank exposures among 1800 banks, we find strong evidence of tiering in the German banking system. Moreover, bankspecific features, such as balance sheet size, predict how banks position themselves in the interbank market. This link provides a promising avenue for understanding the formation of financial networks.
Keywords: G21; L14; D85; C63; 330; interbank markets; intermediation; networks; tiering; core and periphery; market structure; Geldmarkt; Bank; Unternehmensnetzwerk; Kern-Peripherie-Beziehung; Finanzintermediär; Schätzung; Deutschland